Sustainable Palm Oil Industry: A Literature Study with Bibliometric Analysis - Saleh Husin; Chandra Wijaya; A. Hanief Saha Ghafur; T.M. Zakir Machmud (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This article aims to discuss the latest trends and look for new research on the sustainable palm oil industry. This research is a literature review using Publish or Perish software to search for article data on Google Scholar and using VOSviewer to analyze and visualize the data obtained. The research findings show 3 main group themes of research on the sustainable palm oil industry and based on the research findings, the researcher draws the conclusion that the research gap on the sustainable palm oil industry is still very wide open for the theme of the institutional industry, producers, and the European Union as well as on the palm oil certification system, especially in Indonesia.